Sprinkler fitting (Wheels of learning, 1996)
This exceptionally produced trainee guide features a highly illustrated design, technical hints and tips from industry experts, review questions and a whole lot more Key content includes Orientation to the Trade, Introduction to Components and Systems, Steel Pipe, CPVC Pipe and Fittings, Copper Tube Systems and Underground Pipe